THE CONCEPT OF THE CREATION OF THE UNIVERSE IN ISLAM AND CHRISTIAN - Irfan, irfan (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
This study aims to analyze the concept of the creation of the universe from the Islamic view through the interpretation of Ibn Katsir and the Christian view through the Bible. This study uses qualitative research methods. Based on Ibn Katsir's view, the universe's creation consists of several processes. Firstly, Allah created the earth in two days, then created the sky in the next two days, then spread out the earth in the last two days. In the last process, Allah brings out water, plants, mountains, sand, inanimate objects, hills, and everything between the sky and the earth. According to the Bible, the process of creating the universe also consists of six days. Day and night were created on the first day. On the second day, the sky was created. On the third day, the earth was created. The stars and sun were created on the fourth day. On the fifth day, creatures in the water and the sky were created. All kinds of animals were created on the sixth day, and humans were created on the last. The seventh day is God's rest/rest day. Thus, it can be concluded that there are similarities and differences between Islam and Christianity in the concept of the creation of the universe.